Social Economy and Gender Equality on the Labour Market - Domagała, Wiktoria (Studia Oeconomica Posnaniensia, 2015)
The article discusses the issue of actions towards the establishment of equal opportunities for women and men on the Polish labour market undertaken by social economy organizations. The analysis shows the theoretical aspects of social economy entities. Then it focuses on the social and economic dimensions of the social economy's impact on gender inequality. In order to provide an economic background the paper presents the basic statistical data on the economic activity of the population by sex in the years 1993-2013 on the Polish labour market. Next, the article focuses on projects run by social economy, that take issues, e.g. work-life balance, flexicurity, into consideration. The article identifies innovative cross-sectoral actions aimed at eliminating barriers for women's economic activity. The gender perspective is adopted as a determinant for projects implemented by the social economy. Their main features, range of impact and potential barriers are illustrated in the essay. Furthermore the article recommends areas of gender inequality that can be a challenge to initiatives undertaken by the social economy.